A survey of Chinese literature on the management of technology and innovation, 1987-1997. (1st January 2001) - White, Steven; Liu, Xielin; Xie, Wei
This paper reviews 98 Chinese language articles in order to introduce a growing body of research that investigates technology and innovation management issues in China's rapidly evolving transition economy, a context only recently receiving attention in the English literature.